Aesthetic Medicine Art and Techniques - Prendergast, Peter M.; Shiffman, Melvin A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The Aesthetic Medicine: Art and Techniques provides step-by-step instructions in the procedures and techniques commonly employed in aesthetic medicine. The book is divided into four parts, the first two of which offer an introduction to aesthetic medicine and discuss preoperative assessment and treatment. Detailed guidance is then given on a wide range of cutaneous procedures, including the use of botulinum toxins, dermabrasion and microdermabrasion, cryotherapy, chemical peel skin resurfacing, laser treatments, mesotherapy, sclerotherapy, capacitive radiofrequency treatment, and the use of dermarollers. The final part of the book is devoted to techniques employed in shaping the face and body, such as breast and facial augmentation, penile enhancement, liposuction, and management of hair loss or excess hair. All procedures are depicted with the aid of numerous high-quality illustrations and color photographs. This book will serve as an excellent guide for both beginners and experienced practitioners.
From the contents: AESTHETIC MEDICINE -- Defining -- Ethical Aspects -- PREOPERATIVE -- Clinical Assessment Of Facial Aging -- Weight Management -- Phytotherapy -- Skin Imaging -- Cosmeceuticals For Maximizing Treatment Of The -- Aging Face -- CUTANEOUS PROCEDURES -- Local Regional Anesthesia -- Botulinum Toxins -- Microdermabrasion -- Dermabrasion -- Cryotherapy -- Chemical Peel Skin Resurfacing -- Fractional Laser Resurfacing -- Facial Rejuvenation With Poly-L-Lactic -- Acid (Sculptra) -- Intense Pulsed Light (Ipl -- Laser Treatment -- Sclerotherapy Varicose Veins -- Cellulite: Etiology, Classification, Pathology, -- And Treatment -- SHAPING FACE AND BODY -- Breast Augmentation With Hyaluronic Acid -- Potential Risks And Complications Of Injectable Alloplastic Facial Fillers -- Facial Augmentation With Autologous Fat -- Lipoplasty of The Face Using Vaser -- Suture Lifting Techniques -- Emerging Technologies -- Index.
Keywords: Medicine; Dermatology; Otorhinolaryngology; Head -- Surgery; Surgery; Medicine & Public Health; Plastic Surgery; Dermatology; Otorhinolaryngology; Oral and Maxillofacial Surgery; Head and Neck Surgery